2015
DOI: 10.1001/jamasurg.2015.1121
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Among Injured Children Treated at Different Trauma Center Types

Abstract: Injured children treated at ATCs and MTCs had higher in-hospital mortality compared with those treated at PTCs. This association was most evident in younger children and remained significant in severely injured children. Quality improvement initiatives geared toward ATCs and MTCs are required to provide optimal care to injured children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
144
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 30 publications
3
144
2
1
Order By: Relevance
“…Patients treated at PTCs were younger, more likely to be transferred from other hospitals, less severely injured, and had a different distribution of injury mechanisms. The demographic and injury severity differences are consistent with most previous studies including data from children of all ages 3,9,16,23 and those containing only adolescent data. 13,14 The patient population differences observed between those treated at PTCs and either ATCs or MTCs may be explained by either first-responder triage decision making or local triage criteria.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Patients treated at PTCs were younger, more likely to be transferred from other hospitals, less severely injured, and had a different distribution of injury mechanisms. The demographic and injury severity differences are consistent with most previous studies including data from children of all ages 3,9,16,23 and those containing only adolescent data. 13,14 The patient population differences observed between those treated at PTCs and either ATCs or MTCs may be explained by either first-responder triage decision making or local triage criteria.…”
supporting
confidence: 89%
“…Previous studies examining the optimal trauma center type for children have mostly shown an outcome advantage for children treated at a PTC or MTC compared with those treated at an ATC. [3][4][5][6][7][8][9] Although a consensus is forming for the optimal treatment center for younger children, controversy still remains about the optimal location for treating injured adolescents. [10][11][12][13][14] Few studies have evaluated the outcome for adolescents at different trauma center types after injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The management of injured children continues to evolve, with the establishment of level 1 pediatric trauma centres 3 and centralization of care with involvement of multiple disciplines. 4,5 Given that the management of severely injured children requires coordinated care provided by multiple pediatric surgical subspecialties, 2,5,6 we sought to describe the frequency, timing, associated costs and surgical subspecialties involved in the management of pediatric trauma patients at a regional lead trauma hospital in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates included race, insurance status, Trauma Mortality Prediction Model (TMPM) predicted mortality, 27 admission hypotension, abnormal admission HR, abnormal admission RR, admission GCS, ICU admission, need for mechanical ventilation, urgent operation, occurrence of in-hospital complications, non-accidental trauma, and trauma center type (adult only level I/II, pediatric only level I/II, mixed adult/pediatric level I/II, non-level I/II center). Given recent evidence that trauma center type influences mortality in children, 28 interactions were tested between transport mode and trauma center type as well as trauma center level to determine if the effect of transport mode on survival differs across these factors. Discharge disposition models were also adjusted for presence of an extremity injury with abbreviated injury scale (AIS)>2 and presence of a spinal cord injury.…”
Section: Methodsmentioning
confidence: 99%